2021
DOI: 10.1111/jcap.12329
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric nurse delivered group‐cognitive‐behavioral therapy for internalizing behavior problems among children of parents with alcohol use disorders

Abstract: Purpose The present study aimed at assessing the effectiveness of group‐cognitive‐behavioral therapy for anxiety, depression, and self‐esteem among children of parents with alcohol use disorder. Design and Methods A randomized, controlled trial study was conducted with 70 children of parents with alcohol use disorder. The children were initially screened for the presence of behavioral problems and living with parents with alcohol use disorder, then assigned randomly to experimental and control groups. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Prior studies show that the scale had high internal consistency (α = 0.72–0.87), and test–retest reliability for the 2-wk interval was 0.85, and for the 7-mo interval, 0.63[ 23 , 27 ]. Prior Indian studies have used this scale to measure global self-worth[ 4 , 7 ]. Reliability for the present study was established by test–retest method(α = 0.91) and split-half method (α = 0.81).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies show that the scale had high internal consistency (α = 0.72–0.87), and test–retest reliability for the 2-wk interval was 0.85, and for the 7-mo interval, 0.63[ 23 , 27 ]. Prior Indian studies have used this scale to measure global self-worth[ 4 , 7 ]. Reliability for the present study was established by test–retest method(α = 0.91) and split-half method (α = 0.81).…”
Section: Methodsmentioning
confidence: 99%
“…Reliability for the SCAS has been tested across a wide range of studies and consistently showed a very high internal reliability (α = 0.87–0.94)[ 28 , 29 ]. Several Indian studies have utilized this scale to assess anxiety among children aged 11–16 years[ 4 , 7 ]. Reliability for the present study was established by test–retest method using Cronbach‘s α = 0.92 and split-half method using Pearson’s r (0.88).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature reviews published in the past two decades have validated the technical and interpersonal skills of mental health nurses, affirming their effectiveness in treating individuals with moderate to severe mental health issues (Hurley et al., 2022). The scope of mental health nurses’ psychotherapeutic roles encompasses a variety of areas such as palliative care, geriatric care, diabetes, alcohol abuse, self‐harm, suicidality, perinatal care, infertility, neonatal care, lung cancer, treatment of schizophrenia and management of multimorbidity, including depression and anxiety in primary care settings (Abujelban et al., 2023; de Pinho et al., 2020; Hayashi & Onishi, 2021; Kappelin et al., 2022; Li et al., 2022; Malakian et al, 2022; Maleki et al., 2022; Omkarappa et al., 2021; Popp et al., 2022; Sampson, 2023; Sass et al., 2022; Sharifipour et al., 2022; Sriati et al., 2023; van Klinken et al., 2023; Vlachou et al., 2022; Yanık & Kavak Budak, 2023).…”
Section: Development Of Ptn Worldwidementioning
confidence: 99%